Feeding Propensity and Cannibalism of Micraspis Discolor (Fab.) to Different Prey Species (Aphis craccivora and Nilaparbata lugens) under Laboratory (Journal of Environmental Science and Natural Resources, 2016)
Feeding propensity and cannibalism of Micraspis discolor (Fab.) to different prey species (bean aphids and brown plant hopper ) was studied in the laboratory of the Department of Entomology, Bangladesh Agricultural University, Mymensingh, during January, 2007 to April, 2007. It was found that the highest pre-oviposition period was to 5.6±0.54 days when BPH were used and this period was lowest, 4.6±0.54 days using bean aphid. The oviposition period was maximum 40.20±1.78 days using bean aphid and minimum 29.00± 2.00 days were found using BPH. Maximum number of eggs 216.00±16.58 was laid when fed on bean aphid. The hatching percent was highest 88.71% using bean aphid and hatching percent was lowest 85.34% when fed on BPH. Incubation period varied from 2.40±0.54 to 3.80±0.44 days using different foods. However, the larvae passed through four larval instars and highest larval period was 10.00 ± 0.70 when BPH were used as food and lowest was 8.40 days feeding on bean aphid. Pupal period was 3.00±0.00 & 3.80±0.44 days when bean aphid & BPH were supplied as food. The average longevity of female was 38.60±3.78 and 31.40±2.96 days and that of male was 32.00±2.91 & 26.00±0.91 days when feeding on bean aphid and BPH respectively. It was significant at 1% level. The sex ratio of male and female was found (0.78:1.00) using different foods and these were not significant at 1% level. By this experiment, It was observed that feeding propensity of Micraspis discolor to different prey species during the total life cycle was as follows: bean aphid > BPH. It was also found that M. discolor had cannibalistic behavior and this was significant at 1% level.J. Environ. Sci. & Natural Resources, 9(1): 81-85 2016